Effects of Hydroxychloroquine as an Add-on to Conventional Therapy In Patients With Diabetic Nephropathy: A Randomized Controlled Trial (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Hydroxychloroquine (HCQ) has been found to have antithrombotic, lipid-lowering and glucoselowering properties that make it useful in treating a variety  of  chronic diseases, including rheumatoid arthritis and systemic lupus erythematosus. Recently various study also showed its anti proteinuric andrenoprotective effects. To evaluate the effecacy of HCQ as an add on to the conventional therapy of Diabetic Nephropathy (DN).   Materials and methods: This open label randomized controlled trial was conducted at the Chittagong Medical College Hospital in Chattogram at the Nephrology  Department. Sixty patients of DN were enrolled as per  selection criteria into  two groups, in one group 30 patients were started HCQ (100 mg twice daily) along with conventional treatment of DN (Experimental group). In other group 30 patients were started with conventional treatment without HCQ (Control group). They were followed up after 3 rd  and  6 th  month of  initiation of  the treatment. Both groups were followed upfor any significant changes in their renal function, proteinuria, glycaemic status and lipid profile.Results: At the end of six months there was almost 8.9% reduction of  serum creatinine in experimental group while it increased  in control  group around  22.2% both of which were significant (p